Meningkatkan Keamanan Data Dalam Berbagi File Menggunakan Kriptografi Asimetris Elliptic Curve Cryptography P-521 - Ramadhan, Ashry; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Cryptography has been aplicated into securing information. Cryptography divided into two types, Symmetric and Asymmetric Cryptography. Symmetric Cryptography commonly used for encrypt a file, while Asymmetric Cryptography used for create public key and private key for key exchange.. Elliptic Curve Cryptography (ECC) is the one of asymmetric cryptography that is commonly used for create a secure public and private key depending on the bit length of ECC, in this research use 521-bit length. Advanced Encryption Standard (AES) is the one of symmetric cryptography has been used as a standard for securing private data, in this research use 256-bit length. AES and ECC are provided by National Security of Standards and Technology (NIST) as a standard for national security applications. The system in this research created into Web Application base using HTML5, CSS3, and JavaScript. The results obtained from this research is the system can encrypt and decrypt any type of file like systems, videos, documents, images and audios file and has avalanche effect property.Keywords: Securing Information, Cryptography, ECC P-521, AES-256, Web Application